2012
DOI: 10.1074/jbc.m111.272427
|View full text |Cite
|
Sign up to set email alerts
|

Nurr1 Protein Is Required for N-Methyl-d-aspartic Acid (NMDA) Receptor-mediated Neuronal Survival

Abstract: Background:The mechanism involved in activity-dependent survival of neurons in the central nervous system is not fully understood. Results: Nurr1 is involved in excitatory transmission-dependent survival of glutamatergic neurons by acting downstream CREB and upstream of BDNF. Conclusion: Nurr1 activation mediates activity-dependent survival of glutamatergic neurons. Significance: A novel function of Nurr1 in activity-dependent survival of glutamatergic neurons is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 59 publications
4
63
0
Order By: Relevance
“…A possibility could be a differential effect downstream ERK. One of the main cytosolic ERK substrates is p90Rsk that directly phosphorylates the cAMP-response element-binding protein (CREB), perhaps the most important transcription factor related to activity-dependent neuronal survival in general and for CGNs survival in particular (30,39). However, we have observed that both NMDA and K25 are able to activate p90Rsk and CREB (Ref.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A possibility could be a differential effect downstream ERK. One of the main cytosolic ERK substrates is p90Rsk that directly phosphorylates the cAMP-response element-binding protein (CREB), perhaps the most important transcription factor related to activity-dependent neuronal survival in general and for CGNs survival in particular (30,39). However, we have observed that both NMDA and K25 are able to activate p90Rsk and CREB (Ref.…”
Section: Discussionmentioning
confidence: 61%
“…The involvement of this pathway in NMDA-mediated survival of CGNs was also reported previously in immature CGNs at 4 DIV (12). It has also been described that BDNF release mediates NMDA pro-survival effect on CGNs (26,30,36,37) and BDNF also promote CGNs survival through activation of PI3K/Akt (13). Thus it is likely that, although NMDA receptor stimulation could activate this pathway directly (35), NMDA-mediated activation of Akt is due to BDNF-mediated stimulation of its receptor.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, CREB target genes Nr4a1 and Nr4a2 expression as well as promoter acetylation are selectively increased after TSA inhibition (Vecsey et al, 2007). Interestingly, Nr4a2 binds to Bdnf promoter 4, and silencing Nr4a2 by shRNA leads to a decrease in BDNF protein levels and a reduction of the effect of NMDA in neuronal survival (Barneda-Zahonero et al, 2012). CREBdependent neuroprotection has also been shown to be mediated by NR4A orphan receptors (Volakakis et al, 2010).The Creb promoter itself changes acetylation status after learning.…”
Section: What Are the Genes Affected By Changes In Histone Acetylatiomentioning
confidence: 99%
“…Cascade-Numerous studies have demonstrated that appropriate activation of NMDAR activates prosurvival molecules (such as CREB) and supports neuronal survival (17,(25)(26)(27). NMDAR overactivation results in significant cell death.…”
Section: Both Glun2a and Glun2b Are Involved In Nmdar-mediated Bidirementioning
confidence: 99%